Areas of Proof in a Discharge Case (Relations industrielles / Industrial Relations, 1960)
SummaryA discharge case involves two areas of proof; a) proof of wrong doing on the part of the grievor, and b) an evaluation of the punishment in relations to the infraction. In this case, there was cause for discipline but not for the extreme penalty of dismissal.Exerpt from an award in a dispute between Dominion Engineering Works Ltd and Lodge 1660, The International Association of Machinists. H. D. Woods, President; J. R. Cardin, Union nominee; H. McD. Sparks, Company nominee. Revue Légale, octobre 1960, pp. 474-485.